2014
DOI: 10.1177/0021955x14525959
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, mechanical properties, and shape memory effects of poly(lactic acid)/ thermoplastic polyurethane blend scaffolds prepared by thermally induced phase separation

Abstract: Novel blended scaffolds combining biobased polylactic acid (PLA) and thermoplastic polyurethane (TPU) were fabricated by thermally induced phase separation (TIPS) using two different solvents. Pure PLA and TPU polymer scaffolds using 1,4-dioxane as the sole solvent exhibited typical ladder-like structures, while blended PLA/TPU scaffolds using the same solvent showed a more uniform microstructure. When de-ionized water was added to the solution as a non-solvent, scaffolds with the mixed solvent showed more ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Distinctive IR bands of TPU in the literature were OC―N―H amide band (in the urethane) at 1220, 1530 cm −1 , ―NH amine band (in the urethane) at 1528–1504 cm −1 , ―CC in aromatic rings at 1475–1600 cm −1 , and ―NCO isocyanate group at around 2340 cm −1 . The IR spectrum of PLA/TPU blend in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Distinctive IR bands of TPU in the literature were OC―N―H amide band (in the urethane) at 1220, 1530 cm −1 , ―NH amine band (in the urethane) at 1528–1504 cm −1 , ―CC in aromatic rings at 1475–1600 cm −1 , and ―NCO isocyanate group at around 2340 cm −1 . The IR spectrum of PLA/TPU blend in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lots of polymers have been used, among which it is worth to mention polylactic acid [18], polyurethane [19], polycaprolacton [20], etc. the metastable region, where a (quite slow) mechanism of nucleation and growth takes place, leading to (relatively) large pores.…”
Section: Thermally Induced Phase Separation (Tips) Techniquementioning
confidence: 99%
“…More recently, biodegradability of the blend has also been reported . To date, a few studies were reported on the TPU/PLA blend foams with focus on preparation of porous scaffold and shape memory foam …”
Section: Introductionmentioning
confidence: 99%